The Role of Oral Fusobacterium nucleatum in Female Breast Cancer: A Systematic Review and Meta-Analysis - Fariah I. Gaba; Raquel Carcelén González; Raquel González Martïnez (Hindawi Limited, 2022)
Introduction. Breast cancer is the world's most prevalent malignancy, with an increasing incidence and a predisposition for postpubertal females from all cultural and ethnic backgrounds. More recently, oral Fusobacterium nucleatum species have been observed in cancerous human breast tissue, drawing attention to the role of microbes in cancer pathogenesis. Objectives. Investigating oral Fusobacterium nucleatum species as potential biomarkers for female-specific breast cancer. Methods. A systematic search in The Central Register of Controlled Trials, EMBASE, EBSCO, NCBI, and MEDLINE databases was undertaken from the 1st January, 1983-31st March, 2022. Articles included were in English and based on women between the ages of 18-96 years with confirmed gingivitis/periodontal disease and breast cancer diagnoses from registered specialists. Authors extracted data independently, and a meta-analysis of risk estimations measuring associations between oral Fusobacterium nucleatum species and female-specific breast cancer was elucidated via calculated relative risks and 95% confidence intervals. Results. AXIS tool analysis revealed 78.70% of articles with a positive correlation between oral Fusobacterium nucleatum and female-specific breast cancer. The risk of breast cancer development increased with significant levels of oral Fusobacterium nucleatum due to gingivitis/periodontitis (relative risk = 1.78, 95% confidence interval = 1.63-1.91). Low-moderate statistical heterogeneity was found (I2 = 41.39%; P = 0.02), and the importance of periodontal status on breast cancer pathogenesis was determined (relative risk = 1.24, 95% confidence interval = 1.01-1.30). Conclusions. Oral Fusobacterium nucleatum species are a risk factor for breast cancer development, thus elevating their biomarker potentiality.